Problems in Road Construction at Local Level - Bhusal, Bidhya; Dahal, Dhundi Raj; Dahal, Kheta Raj (Nepal Journal of Multidisciplinary Research, 2023)
Any nation's infrastructure development encompasses social infrastructure as well as economic infrastructure, or the growth of diverse sectors. Simultaneously created social infrastructure can lead the economic infrastructure in total development at the appropriate level. The capabilities and technical advancement of social infrastructures like retail centers, restaurants, medical facility zones, and schools are well defined, as are the evolving requirements of economic infrastructures like roads, sewage, electricity, open spaces, and gardens. To maintain effective social infrastructure, it is necessary to develop sectors such as education, health, social security, water supply, housing, and sanitation. The study would like to suggest that adequate budget allocation should be conducted during planning process; proper road design, implementation and effective procurement system should be carried out, and management of enough construction materials, suitable equipment, and coordination with local people should be performed. Furthermore, provision of drain while constructing rural road must be included during preparation of DPR along with the watershed management is necessary and establishment of laboratory for material test is necessary in Municipality to assure quality construction along with provision of training for the user committee to provide technical knowledge is necessary.